Novel axial compressive endoprosthesis ACE can enhance metaphyseal fixation and facilitate osseointegration: A biomechanical study - Huang, Siyi; Ji, Tao; Tang, Xiaodong; Guo, Wei (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Metaphyseal fixation for endoprosthetic reconstruction after bone tumor resection is difficult due to short residual bone length and reverse funnel shape of metaphysis. In the current study, 3D printed axial compressive endoprosthesis (ACE) with a short stem and intramedullary axial compressive mechanism is proposed to improve metaphyseal fixation. The rationales of ACE are that (1) intramedullary axial compress enhances stability of endoprosthesis and facilitate bone ingrowth at osteotomy site; (2) 3D printed porous metallic surface at osteotomy surface and stem allows bone ingrowth to achieve osseointegration. Methods: A biomechanical study was performed to explore the initial stability using Sawbones. A diaphysis and metaphyseal segmental defect was created and four fixation structures were simulated: (1) ACE; (2) ACE + lateral plate; (3) stem prosthesis + unilateral plate; (4) stem prosthesis + bilateral plates. Bending and torsional stiffness were determined with a material testing machine. Relationship between torque of compression nut and axial compression force of the bone-implant surface was measured using a round gasket load sensor. Results: ACE + lateral plate was the stiffest in bending test (sagittal 324.3±110.8N/mm, coronal 307.7±8.7N/mm). ACE + lateral plate and stem prosthesis + bilateral plates had the highest torsional stiffness (10.9±1.3Nm/° and 10.7±0.2Nm/° respectively). The bending stiffness of ACE was equivalent to stem prosthesis + bilateral plates (sagittal 196±10N/mm vs 200±7N/mm, coronal 197±14N/mm vs 209±3N/m), but the torsional stiffness of ACE was inferior to stem prosthesis + bilateral plates (6.1±1.3Nm/° vs 10.7±0.2Nm/°). Stem prosthesis + unilateral plate was the least stiff both in bending and torsion. The relationship between torque (T/Nm) and axial pressure (F/N) was F = 233.5T. Conclusion: The axial compressive design of ACE enhances primary stability and facilitate osseointegration, which provides an alterantive option of metaphyseal fixation for endoprosthetic reconstruction.